Research and graduate studies in Geography in Brazil – some reflections - DOI: 10.5752/P.2316-1752.2009v16n18/19p313 - Abreu, João Francisco de (Cadernos de Arquitetura e Urbanismo, 2010)
Abstract This is part of a lecture delivered to summer-school students in 2008 (University of Bologna/PUC Minas). The central theme concerns Research and Graduate Studies in Geography in Brazil, besides some basic concepts of geographic science in today’s world. The second part of the presentation is stored in its totality. Key words: Graduate Studies; Geography; Brazil. GIS.